PENGEMBANGAN LKPD BERBASIS PENDEKATAN DISCOVERY LEARNING PADA PEMBELAJARAN TEMATIK TERPADU KELAS V SEKOLAH DASAR - Marcelina, Shella; Melindawati, Silfi (Jurnal Ilmiah Aquinas, 2021)
This research is motivated by observations, that the LKPD used is still insufficient in inviting active students in the learning process, as well as developing social, emotional, moral and aesthetic communication in children. The problems studied are: 1. How is the development of Student Worksheet (LKPD) based on the Discovery Learning Approach in Integrated Thematic Learning Theme 9 Sub-theme 1 Class V SD Negeri 12 Pisang Padang City; 2. What is the validity, effectiveness, and practicality of Student Worksheet (LKPD) Based on the Discovery Learning Approach in Integrated Thematic Learning Theme 9 Sub-theme 1 Class V SD Negeri 12 Pisang Kota Padang?.This research and development resulted in LKPD products based on discovery learning approaches on the theme of 9 sub-themes 1 and obtained valid / feasible and practical product results for use, the LKPD products developed had fulfilled the components as good teaching materials for use in the learning process because they were in accordance with KI, KD and the suitability of attractive colors, images, sizes and fonts. In addition, according to students' circumstances, the language used is easy to understand, has learning instructions and an assignment assessment score. The form of the assignment is simple but able to cover all learning indicators. From the results of the assessment of the overall average score on the LKPD validation is 84.3 including in the very valid category, it can be used without revision. This shows that the developed LKPD is valid. Thus, it means that the developed LKPD is good and can be used as a learning resource for students in the development of LKPD based on the discovery learning approach in integrated thematic learning in class V elementary schools. The level of practicality of the product is seen from the results of the responses of 1 class teacher, 5 students and their parents with an average score of 95% (Very Interested), which means that the LKPD products developed are practical for use.